2010
DOI: 10.1186/1744-9081-6-69
|View full text |Cite
|
Sign up to set email alerts
|

Role of the trigeminal mesencephalic nucleus in rat whisker pad proprioception

Abstract: BackgroundTrigeminal proprioception related to rodent macrovibrissae movements is believed to involve skin receptors on the whisker pad because pad muscles operate without muscle spindles. This study was aimed to investigate in rats whether the trigeminal mesencephalic nucleus (TMnu), which provides proprioceptive feedback for chewing muscles, may be also involved in whisker pad proprioception.MethodsTwo retrograde tracers, Dil and True Blue Chloride, were injected into the mystacial pad and the masseter muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The rat has thus no direct access to (θ w , φ w , ζ w ), though some information may be available through the mesencephalic nuclei [60,61]. Recent studies have suggested that reafferent signals reporting whisking phase could be combined with an efferent copy of whisking midpoint and amplitude to estimate angular whisker position θ w [62,63,64].…”
Section: Where Versus What: Determining Object Location and Contourmentioning
confidence: 99%
“…The rat has thus no direct access to (θ w , φ w , ζ w ), though some information may be available through the mesencephalic nuclei [60,61]. Recent studies have suggested that reafferent signals reporting whisking phase could be combined with an efferent copy of whisking midpoint and amplitude to estimate angular whisker position θ w [62,63,64].…”
Section: Where Versus What: Determining Object Location and Contourmentioning
confidence: 99%
“…Altogether, for the first time, these studies demonstrated that besides the TG, even the Me5 neurons are involved in macrovibrissae innervation, which role we speculated to be related with encoding spatial information relative to vibrissae movements (Mameli et al. , ).…”
Section: Introductionmentioning
confidence: 67%
“…The goal of this part of the study was to investigate whether the Me5 neurons, which, as previously demonstrated responded to spontaneous and artificial movements of the vibrissae (Mameli et al. , ), are also involved in encoding the related kinematic parameters and specifically the direction, frequency, and amplitude of single displacements.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Objects in the environment sometimes move and, for example, when a shrew is hunting crickets it needs to determine both the location and movement of that prey animal to execute an accurate fatal attack (Anjum et al, 2006). Another consideration is that rats have no spindles in their whisking muscles, and therefore do not have accurate proprioception of their whiskers (Diamond et al, 2008; Mameli et al, 2010). Since accurate radial distance estimation is dependent on well characterized contact speed, a signal-based method, such as the contact duration feature approach presented here, is of potentially great importance.…”
Section: Discussionmentioning
confidence: 99%